Histopathology of the intestine of Clarias batrachus L. under Heavy metal stress (Chittagong University Journal of Biological Sciences, 2013)
Histopathological effect of three heavy metals- cadmium, chromium and mercury on intestine of Clarias batrachus L. was studied under laboratory condition. The common histopathological changes that took place under heavy metal exposure were disintegration of mucosal epithelium, hypertrophied epithelial cells, increased number of goblet cells, sloughed off epithelial cells and mucous in the lumen, degeneration of the connective tissue of sub-mucosa and hyperemic blood vessels. .Separation of mucosal epithelium, especially in the villi and increased goblet cells were prominent in Cd-exposed fish. Clumping of the epithelial cells at the base near the basement membrane was prominent in the case of the Cr- and Hg-exposure. Connective tissue degeneration in the lamina propria and submucosa of the intestine and dilated blood vessels with congestion of blood were prominent in the Cr and Hg exposed fish. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13369 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):45-53, 2010